Immobilization of Simulated Borate Radioactive Waste Solution in Cement-Poly(methylmethacrylate) Composite: Mechanical and Chemical Characterizations. (10th September 2013) - Saleh, H. M.; Shatta, H. A.
Abstract : Solidified cured cement blocks containing different concentrations of the borate waste simulate were impregnated using methyl methacrylate monomer having 0.3% by weight benzoyl peroxide as initiator. Then, the polymerization process was completed by heating the impregnated blocks at ≈ 40°C. To define the suitability, range of applicability, and compatibility of the inert matrix used, relevant to the borate waste immobilized, the final radioactive borate waste forms are evaluated on the basis of their mechanical and chemical properties. Some factors that may affect the characterization of the obtained final waste form, for example, concentration of the incorporated borate waste solution simulate, aging of the solid waste form, before immersion, immersion in various leachants, and time of immersion, were followed systematically. It could be stated that cement-poly(methylmethacrylate) composite exhibited better mechanical and chemical characters compared to the cement as a unique matrix for immobilization of borate waste concentrates.